Juan Egaña, precursor de la integración americana - Silva Castro, Raúl (Estudios Internacionales, 1968)
It seems that the time has come to claim a place for Juan Egaña (1768-1836) in the history of ideas of Spanish-speaking America, both because of what he did and planned for Chile and for the persistent study of a form of supranational organization that would have carry out a kind of amphictyonic confederation of states in which none of these lost their autonomy except to the degree necessary to bring supranational articulation to its final consequences. The intellectual kept the idea under study over the years, covered it with new contours and adapted it many times to emerging needs, in line with the news he received about the behavior of the American nations.